Eliminating the cavity defect and improving mechanical properties of TA5 alloy joint by titanium alloy supporting friction stir welding. (September 2021) - Du, Shuaishuai; Liu, Huijie; Jiang, Minghao; Hu, Yanying; Zhou, Li
Abstract: To widen the narrow friction stir welding (FSW) process window of TA5 alloy, titanium alloy supporting friction stir welding (TSFSW) is proposed. Both conventional FSW (CFSW) and TSFSW methods were employed to reveal the formation mechanism of cavity defect, clarify the microstructure evolution in the weld and investigate the performance of TSFSW. Results showed that the prior β grains below the cavity defect were much smaller than the above and a clear converging line of material flow was observed between the varied grains, indicating the cavity defect was flow-related and concerned with the insufficient heat input at weld bottom. It was found that the stir zone (SZ) could be divided into the contaminated zone (CZ) and the non-contaminated zone (NCZ) according to whether the β-stable tool elements were introduced during welding. The transformed microstructure consisting of α laths, equiaxed α grains and retained β was detected in the CZ, resulting in extremely high microhardness. The NCZ, where the peak temperature was below α-β transus temperature, was composed of refined equiaxed α grains due to the occurrence of dynamic recrystallization. The cavity defect downgrades the mechanical properties of joint by determining the fracture mode. Without complicated devices and preparations, the TSFSW method is capable of obtaining defect-free joint under higher welding speed by reducing the heat dissipation from weld bottom, thereby improving mechanical properties and widening the parameter range.